Population structure of Cotylelobium melanoxylon within vegetation community in Bona Lumban Forest, Central Tapanuli, North Sumatra, Indonesia - ARIDA SUSILOWATI; HENTI HENDALASTUTI RACHMAT; DENI ELFIATI; CUT RIZLANI KHOLIBRINA; YOSIE SYADZA KUSUMA; HOTMAN SIREGAR (Society for Indonesian Biodiversity, 2019)
Abstract. Susilowati A, Rachmat HH, Elfiati D, Kholibrina CR, Kusuma YS, Siregar H. 2019. Population structure of Cotylelobium melanoxylon within vegetation community in Bona Lumban Forest, Central Tapanuli, North Sumatra, Indonesia. Biodiversitas 20: 1681-1687. In many forests stand, Cotylelobium melanoxylon is hard to find in the wild at present day because its bark has been intensively harvested for traditional alcoholic drink and sold by kilogram in traditional market in North Sumatra and Riau. This activity has put the species into serious threats of their existence in their natural habitat. We conducted study to determine the population structure of the species at seedling to tree stage in Bona Lumban Forest, Central Tapanuli. We used purposive sampling by making line transect at forest area where C. melanoxylon naturally grow. There were four transects with each transect consisted of five plots in which nested plots were established to record data at four growth stages, resulting in 80 plots in total. The result showed that the Important Value Index (IVI) for C. melanoxylon were 66.33, 17.65, 11.82, 12.90; Diversity Index (H) were 2.9, 1.90,2.88, 2.53 and 12.90, Index of evenness (E) were 0.844, 0.534, 0.85, 0.935 and the Index of Richness (R) were 5.71, 7.13, 5.37, 3.67 for the stage tree, pole, sapling, and seedlings, respectively This result demonstrates that C. melanoxylon still grows naturally in Bona Lumban at all stages from tree to seedling. However, there might be a problem in its natural regeneration as there is big difference of its high IVI at tree stage compared to IVI value for its younger stages. The regeneration status of C. melanoxylon was also classified into fair. This might be generated from the condition that the existing mature trees remaining were no longer productive and healthy due to excessive harvesting for its bark.